ON THE VISCOSITY OF NATURAL GAS (Journal of Sciences, Islamic Republic of Iran)
The existing measuremenJs of the viscosity of gaseous systems can be extended if use is made of statistical mechanics. In this work, we confine ourselves to the measurements of the viscosity of multicomponent mixtures of low-density gases. The method is applied to one sample of natural gas.